Analysis of Total Phenolic and Flavonoid Levels in Carrot (Daucus carota L.) Extract with Different Solvents Polarity - Afrellia, Rika Eka; Puspitasari, Anita Dwi (Universitas Negeri Semarang, 2023)
Carrot (Daucus carota L.) contains phenolic and flavonoid compounds that contribute to various pharmacological activities. Phenolic and flavonoids can be extracted using various solvents. Solvent polarity difference will produce amounts and types of secondary metabolites differently. This research aims to compare the total phenolic and flavonoid content of carrot extract from various solvents. Carrot was extracted using the maceration method with n-hexane, ethyl acetate, and 70% ethanol as solvent to obtain n-hexane, ethyl acetate, and 70% ethanol extract of carrot. Spectrophotometry carried out the determination of total phenolic content by comparing gallic acid and total flavonoids with a comparison of quercetin. The maximum wavelength of gallic acid is 739.60 nm and the operating time of 120 minutes. The maximum wavelength of quercetin is 427.50 nm and an operating time of 30 minutes. Total phenolic and flavonoid levels of carrot extract from the three solvents were analyzed statistically through one-way ANOVA followed by the Bonferroni test at a 95% confidence level. The results showed that the total phenolic contents of the n-hexane extract, ethyl acetate, and 70% ethanol extract of carrot 11.881±0.31; 24.308±1.33 and 39.398±1.65 mg GAE/g extract. The flavonoid content was 2.650±0.13; 20.675±2.58 and 9.063±0.99 mg QE/g extract respectively. The highest total phenolic content was obtained from 70% ethanol solvent and the highest total flavonoid was obtained from ethyl acetate solvent.